2021
DOI: 10.1108/dat-10-2020-0069
|View full text |Cite
|
Sign up to set email alerts
|

Increased propensity for violence among female jail detainees with PTSD, panic disorder and alcohol use disorder

Abstract: Purpose The female jail population is steadily growing in rural jails across the country. Detainees have high rates of mental health and substance use disorders, some of which are linked to violent offenses. These conditions include post-traumatic stress disorder (PTSD), panic disorder (PD) and alcohol use disorder (AUD). This study aims to examine the associations between these disorders among females charged with violent offenses. Design/methodology/approach The sample consists of 167 female detainees from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…As noted above, prior research has indicated that PTSD is associated with increased risk for violent offending (Blakey et al, 2018; E. N. Taylor et al, 2020; S. L. Taylor et al, 2021).…”
Section: Introductionmentioning
confidence: 87%
“…As noted above, prior research has indicated that PTSD is associated with increased risk for violent offending (Blakey et al, 2018; E. N. Taylor et al, 2020; S. L. Taylor et al, 2021).…”
Section: Introductionmentioning
confidence: 87%